A Leading Role of Stem Cells in Breast Malignant Cells - Sarvananda, L. (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
A momentous evolution has been made in describing cellular hierarchy and the stem cell (SC) niche in the human mammary gland. Mammary stem and progenitor cells exist in two different states: Epithelial and mesenchymal. Several features of the mammary SCs predispose them to play a critical role in breast cancer (BC) initiation, progression, and metastasis. Signaling pathways contributing to the self-renewal, such as Wnt, Notch, Hh, and bone morphogenetic protein, have been shown to be linked with BCSCs. Furthermore, biomarkers connected with stemness, such as CD44, CD24, epithelial cell adhesion molecule, and ALDH1, have been identified and used to characterize these cells. In addition, many different miRNA families and micro environmental factors were shown to regulate a lot of cancer SCs (CSC) properties and maintain their stemness. All these findings have started a new era of BC research. In the present BC, SCs have become the targets of BC therapy, although the tests are mainly on the basic stage level. Since the CSCs are able to escape chemotherapy and are resistant to drugs, radiotherapy and apoptotic processes, the therapeutic targeting is mostly concentrated on the disruption of survival signaling pathways and the use of modern technology, like nanotechnology.